Guided Bone Regeneration of Femoral Segmental Defects using Equine Bone Graft: An In-Vivo Micro-Computed Tomographic Study in Rats - Mohammed Awadh Binsalah; Sundar Ramalingam; Mohammed Alkindi; Nasser Nooh; Khalid Al-Hezaimi (Journal of Investigative Surgery, 2019)
Background and objectives: Guided bone regeneration (GBR) is commonly used for osseous defect reconstruction. The objective of this study was to evaluate in real-time (in-vivo) the efficacy of equine bone graft for GBR in segmental critical-size defects (CSD) of the femur in a rat model. Materials and methods: Following ethical approval, 30 male Wistar-Albino rats (age 12–14 months/weight 450–500 grams) were included. Under general-anesthesia, a mid-diaphyseal segmental CSD (5 mm) was created in the femur and stabilized using titanium Miniplate(4 holes,1.0 mm thickness). Depending upon material used for GBR, animals were randomly divided into three groups(n = 10/per group). Negative control-Defect covered with resorbable collagen membrane(RCM); Positive control-Defect filled with autologous bone and covered by RCM; Equine bone-Defect filled with equine bone and covered by RCM. Real-time in-vivo Micro-CT was performed at baseline, 2, 4, 6 and 8 weeks to determine volume and mineral density of newly formed bone (NFB) and remaining bone graft particles (BGP). Results: In-vivo micro-CT revealed increase in volume and mineral density of NFB within defects from baseline to 8-weeks in all groups. At 8-weeks NFB-volume in the equine bone group(53.24 ± 13.83 mm3; p < 0.01) was significantly higher than the negative control(5.6 ± 1.06 mm3) and positive control(26.07 ± 5.44 mm3) groups. Similarly, NFB-mineral density in the equine bone group(3.33 ± 0.48 g/mm3; p < 0.01) was higher than the other (negative control–0.27 ± 0.02 g/mm3; positive control–2.55 ± 0.6 g/mm3). A gradual decrease in the BGP-volume and BGP-mineral density was observed. Conclusion: The use of equine bone for GBR in femoral segmental defects in rats, results in predictable new bone formation as early as 2-weeks after bone graft placement.